Factors affecting adventitious rooting and sprouting in Hyptis australis (Lamiaceae) cuttings - Ríos, María Rita (2022)
Hyptis australis is a species of the Lamiaceae family, endemic to the Atlantic Forest, whose conservation status is critical and its potential benefits for the ecosystem and society are still unknown. For rescue and conservation purposes (ex situ/in situ), the need arises to generate a vegetative propagation protocol to facilitate and increase the availability of plants. With this objective, factors such as the type of substrate, type of stake and hormone were studied. One-year-old plants were used, obtained from seeds harvested from plants located in the southern region of the province of Misiones (Argentina). Apical and subapical cuttings were used in two trials, the first studied the feasibility of inducing adventitious roots in pine bark, sand and perlite substrates. In the second test, the induction of rhizogenesis was evaluated in cuttings treated for 30 minutes with a solution of 100 mg.kg-1 of naphthalenacetic acid (ANA) or indole butyric acid (IBA) in pine bark. The best results were obtained in the sand substrate and in the terminal stakes. ANA was the hormone that generated the highest percentage of apical cuttings (80.00±14.14%) and subapical (84.00±16.73%) with roots. In the subapical cuttings the sprouting percentage was higher in both experiments. The probability that an H. australis cuttings will develop adventitious roots depends on the type of substrate, but the addition of ANA notably improves the rooting percentage.